2017
DOI: 10.22146/ijc.23620
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Carboxyl and Hydroxyl Groups of Humic Acid in Removing AuCl<sub>4</sub><sup>-</sup> from Aqueous Solution

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 50 publications
0
9
0
3
Order By: Relevance
“…Since recoverable sugar content is subordinate to two components of root yield and sugar content, therefore increasing the amount of humic acid consumed can increase recoverable sugar yield by increasing root yield (Rehab et al, 2019). Previous research has shown that the use of humic acid reduces molasses sugar by reducing root impurities (Sudiono et al, 2017).…”
Section: Sugar Contentmentioning
confidence: 99%
“…Since recoverable sugar content is subordinate to two components of root yield and sugar content, therefore increasing the amount of humic acid consumed can increase recoverable sugar yield by increasing root yield (Rehab et al, 2019). Previous research has shown that the use of humic acid reduces molasses sugar by reducing root impurities (Sudiono et al, 2017).…”
Section: Sugar Contentmentioning
confidence: 99%
“…One of the sorbed mechanism metal ions onto functional group in HD-HA is water bridge [27]. This mechanism can be proved from ratio monolayer sorption capacity of Cd(II) and Zn (II) closely match with ratio hydrate radii for Cd(II) and Zn(II), that was 5 : 6.…”
Section: Sorption Isothermmentioning
confidence: 73%
“…Acidity is a function of amount H + in solution medium. It has high effect on the form of chemical substance or metal substance in aqueous medium [27]. Lower pH (high acidity) affects in decreasing the metal ions that attached in active site of sorbent as a result of competition between H + which the consequences is high concentration of unsorbed metal ions in solution.…”
Section: Effect Of Medium Aciditymentioning
confidence: 99%
“…Asam humat hasil ektraksi dari tanah gambut sesuai dengan tatacara yang disarankan oleh the International Humic Substances Society (IHSS), terbukti memiliki kemampuan mengadsorp AuCl4dari dalam larutan. Adsorpsi berlangsung optimum pada pH 2,0 dan proses ini dikendalikan oleh ikatan hidrogen pada gugus -COOH tak-terionisasi sedangkan reduksi Au(III) menjadi logam emas (Au) terjadi karena peran gugus -OH (Santosa et al, 2011;Sudiono et al, 2017). Studi adsorpsi ion Au(III) dengan menggunakan asam humat menggunakan metode batch memiliki kemampuan adsorpsi mencapai 84,05% selama 1500 menit ) Ismillayli et al, (2009 telah mengisolasi asam humat dari tanah gambut Rawa Pening Ambarawa dalam suasana basa.…”
Section: Pendahuluanunclassified